Abstracts from the first Australian conference on mathematics and computers in sport, 1992 (1992)
The use of scientific method in sport is not new. For many years scientists, statisticians, mathematicians and just plain sport enthusiasts have been collecting data with the hope that it will provide some magic formula to increase the chance of success of individuals or teams in sport. The advent of computers has been of immeasurable value in this regard with modern machines now being able to process enormous amounts of information at the touch of a key. The question is just how useful all this research really is when translated into practical terms. The number of sports using computerised statistics is seemingly endless and examples include all codes of football, hockey, basketball, water polo and baseball. Without such evidence players and coaches would have to rely on their own impressions and prejudices in developing their game plans. It seems a fair comment that the scientific analysis of sports performance has not gained the acceptance it should have in Australia. This paper examines some of the reasons why and looks at the work done in several notable sports including tennis, netball and cricket. It also considers the question of just who really benefits from all this research.